Region of confidence measurement for the purpose of localization in wireless sensor networks - Anisur Rahman; K. M. Safin Kamal (Institute of Advanced Engineering and Science, 2026)
Accuracy of localization of the sensor nodes is the key factor for the reliability and efficiency of wireless sensor networks (WSNs). Although a number of localization algorithms have been proposed for WSNs, the major challenge for most real-world applications is the uncertainty of measurements of the references. The proposed work describes a novel approach for estimating the localization accuracy with the help of the region of confidence (ROC), the common region formed from the intersections of the circular regions defined by the distances of numerous reference nodes in a 2D plane. The work investigates the feasibility of localization accuracy with the help of simulations performed for different scenarios with varying distances of the reference nodes. The proposed approach utilizes the ROC technique for providing a measurable significance for the evaluation of localization efficiency for a range of error conditions. This proposed work contributes towards the evolution of efficient localization techniques for real-world environments of WSNs.